2020
DOI: 10.1016/j.clinimag.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Correcting a decade of negative news about mammography

Abstract: It's been ten years since the U.S. Preventive Services Task Force pulled back on recommendations for breast cancer screening in women ages 40-49 years. After a decade of negative reports, most physicians are aware of mammography's limits. Today, many women avoid, delay or deliberately skip getting screened. As invasive breast cancer rates have been rising, and breast cancer remains a leading cause of death, truthful information about screening is critical for public health. Unfortunately, many reports about ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…As molybdenum target X-ray photography has high contrast, high resolution and favorable repeatability and produces clear images of micro-calcifications, it is often used for breast examination, especially the screening of breast cancer[ 17 ]. A conventional X-ray machine, with the tube anode surface made of tungsten, produces short waves, hard X-rays with strong penetrability.…”
Section: Discussionmentioning
confidence: 99%
“…As molybdenum target X-ray photography has high contrast, high resolution and favorable repeatability and produces clear images of micro-calcifications, it is often used for breast examination, especially the screening of breast cancer[ 17 ]. A conventional X-ray machine, with the tube anode surface made of tungsten, produces short waves, hard X-rays with strong penetrability.…”
Section: Discussionmentioning
confidence: 99%
“…The low number of nodal metastasis, and particularly the low rate of SLN macrometastasis found in our study, may be explained by the well-established Swedish National Breast Cancer Screening program, which is available for all Swedish women within the age range of 40–74 years [ 10 , 11 ]. Mammography screening enables the detection of breast cancer at an early stage before palpation is possible.…”
Section: Discussionmentioning
confidence: 98%
“…Since the introduction of a public mammography screening service, the prevalence of breast cancer patients presenting with heavy burden lymphatic metastasis at the time of diagnosis has declined [ 10 , 11 ], and the importance of PMRT for breast cancer patients with minor metastatic burden has been questioned [ 12 ]. For patients with only sentinel lymph node (SLN) micrometastasis (≤2 mm), PMRT is today not routinely recommended [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within the cohort of patients, women aged < 50 and ≥ 70 years showed statistically significantly larger tumours, and these results could be at least partially ascribed to the absence of routine examinations for most of these patients. In fact, previous studies reported that patients who perform routine breast examination show a smaller tumour size at diagnosis [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%